ANALYSIS OF SHADOW TEACHER FOR INCLUSIVE STUDENTS IN FATMA KENANGA ELEMENTARY SCHOOL BENGKULU - anisya triaulia; Washlurachim Safitri; Yupika Maryansyah; 4Agung Suhadi (Teaching English and Language Learning English Journal, 2024)
The purpose of this research is to analyze the role of Shadow Teacher towards inclusive students at Fatma Kenanga Elementary School, Bengkulu City. This research method is descriptive qualitative. The research instrument is in the form of Question Lists which are based on (Skjorten et al 2001). The results of the study, of the 6 roles Shadow Teacher in (Skjorten et al 2001) all the roles of Shadow Teacher for Inclusive Students in Fatma Kenanga Elementary School Bengkulu are applied. There are 6 Shadow Teacher roles in assisting inclusive students, namely, 1) helping students with special needs to re-understand the material delivered by the teacher in class, 2) assisting students with special needs in completing their assignments by providing instructions that are easy understood by students, 3) helping organize activities that can be done inside or outside the classroom, 4) preparing students with special needs students for routine conditions that change prositive routine conditions, 5) emphasizing the success of students with special needs and provide rewards for their efforts, and 6) helping students with special needs in all activities at school that needed. The researchers suggested that the role of Shadow Teacher in assisting inclusive students to be emphasized more because being inclusive students companion required extra skills for the teaching process. For future researcher who are interested in conducting similar research, it is advisable to conduct research on large samples or research subjects and also at other levels of education. Keywords: : Shadow Teacher, Inclusion Children, Shadow Teacher Roles.